Collaborative Governance for Integrated Care: Insights from a Policy Stakeholder Dialogue - Gordon, Dara (Int J Integr Care, 2020)
INTRODUCTION: Integrated care is a goal of many health care systems. However, operationalizing and implementing integrated care remains challenging especially in continuously evolving policy environments. We report on a policy symposium held in 2017 focused on operationalizing a particular integrated care policy in the context of policy evolution in Ontario, Canada. METHODOLOGY: Forty-five participants attended the symposium including government employees, health care leaders, researchers, clinicians, and patient representatives. The symposium included presentations from representatives of each group and breakout sessions. Two trained observers recorded observational field notes. RESULTS: We report four recommendations and fourteen sub-recommendations which arose regarding the implementation of the policy. We highlight four important tensions which characterize challenges regarding its implementation, and discuss the recommendations in the context of Collaborative Governance. DISCUSSION: We outline how the recommendations could be strengthened by collaborative governance and identify where this framework could support governance and leadership challenges associated with implementing integrated care. We describe the unique challenges posed by working towards these goals in an evolving policy environment. CONCLUSION: We draw on collaborative governance to generate insights for leaders implementing integrated care and conclude by addressing the importance of maintaining collaborative governance initiatives under circumstances of unstable policy environments.